Developmental neuropsychological assessment of 4- to 5-year-old children born following Preimplantation Genetic Diagnosis (PGD): A pilot study. Issue 4 (18th May 2016) - Sacks, Gilat Chaya; Altarescu, Gheona; Guedalia, Judith; Varshaver, Irit; Gilboa, Tal; Levy-Lahad, Ephrat; Eldar-Geva, Talia
Abstract : The purpose of this pilot study was to evaluate developmental neuropsychological profiles of 4- to 5-year-old children born after Preimplantation Genetic Diagnosis (PGD). Twenty-seven participants received a neurological examination and a battery of neuropsychological assessments including Wechsler Preschool & Primary Scale of Intelligence - Third Edition (WPPSI-III; cognitive development), Preschool Language Scale, Fourth Edition (PLS-4; language development), Wide Range Assessment of Visual Motor Abilities (visual motor abilities), Childhood Autism Rating Scales II (a screening test for autistic spectrum disorders), and the Miles ABC Test (ocular dominance). Parental questionnaires included the Behavior Rating Inventory of Executive Function Preschool Version (BRIEF-P; executive function), Child Behavior Checklist (CBCL) and the Carey Temperament Scales Behavioral Style Questionnaire (socioemotional development and temperament), and the Vineland Adaptive Behavior Scales, Interview Edition, Second Edition (general adaptive behavior). Subjects' tests results were compared to each test's norms. Children born after PGD demonstrated scores within the normal or above-normal ranges for all developmental outcomes (mean ± SD ): WPPSI-III-VIQ 107.4 ± 14.4 ( p  = .013), PLS-4-Total 113.2 ± 12.4, p  < .001), CBCL-Total 41.1 ± 8.6 ( p  < .001), BRIEF-P-Global Executive Composite 44.8 ± 9.5 ( p  = .009). Twelve (44%) of the PGD children had a significant difference between their VIQ and PIQ scores (compared to 27% in the general population). One subject was found to show possible signs of autistic spectrum disorder, although a family history of autism was noted. In conclusion, in this pilot study, children assessed at age 4–5 years and conceived after PGD displayed developmental neuropsychological outcomes within normal limits as compared to their chronologic peers. A larger study is needed to evaluate and follow the neuropsychological development of children born after PGD.